242 Standardizing Sonographic Descriptors of Peyronie's Plaques. (1st May 2022) - Baird, B; Broderick, G
ABSTRACT: Introduction: Peyronie's Disease (PD) is characterized by a fibrous scar of the tunica albuginea. PD is typically imaged with 2D ultrasound. We propose a classification system of these ultrasound findings in the evaluation of PD. Objective: The purpose of this study is to establish a functional, reproducible sonographic classification system for evaluating PD and to examine the relationship between PD grading and curvature, duration of PD, and vascular erectile status. Methods: In our study, 395 patients with PD underwent intracavernous injection with an erectile agent (ICI) followed by Color Doppler Duplex Ultrasound (CDDU). All CDDU studies were performed by a single examiner and all PD grading was done by two independent reviewers using saved images. CCDU findings including peak systolic velocities (PSV) and resistive indices (RIs) were recorded. PD grades of 2D images were classified into three grades: Grade 1 acoustic shadowing without calcification; Grade 2 focal microcalcifications of the tunica, pillars, or septal fibers; Grade 3 confluent calcification of the dorsal, septal, ventral tunica albuginea. Results: There were 250 patients classified with Grade 1 (63%) sonographic changes, 75 with Grade 2 (19%), and 70 with Grade 3 (18%). Neither median age nor body mass index (BMI) of the cohorts were significantly different: Grade 1 (59.3 yr), Grade 2 (59 yr) and Grade 3 (60.3 yr), p = 0.711; BMI 27.6, 28.2, 27.7, p = 0.813. Medical risk factors for erectile dysfunction, including hypertension, heart disease, diabetes mellitus, hyperlipidemia, smoking history, and history of prostate surgery were not statistically different for the three cohorts. Most patients had previously used PDE5-Inhibitors (293/395). History and or physical findings of Dupuytren's palmar contracture was noted in 30/395 (7.6%) of men. The median duration of PD was not significantly different in the three cohorts (12, 12, 14 months p = 0.639). Neither CDDU diagnoses (Table 1) nor curvature varied by sonographic grades (Table 2). Conclusions: The scar resulting from PD seals together the outer longitudinal and inner circular layers of the tunica albuginea causing deformity of the erect shaft. PD plaques are usually palpable and associated with focal thickening of the tunica. On 2D ultrasound, the typical appearance is an acoustic shadow. Most of our patients presented with Grade I acoustic shadowing and no calcifications 250/395 (63%); on the other hand, 19% had acoustic plaque shadowing and additional findings of focal tunica or deep microcalcifications and 18% had confluent calcification of the dorsal, septal or ventral tunica. We propose a unique and reproducible classification system. This grading system based on grayscale ultrasound of Peyronie's plaques may serve as a paradigm for diagnosis, didactics and integrated research. Disclosure: Work supported by industry: no, by N/A.